Peran Dapur Umum dalam Mendukung Perjuangan Masyarakat Dusun Kemusuk Pada Agresi Militer Belanda II 1949 - Rizal Hidayat; Siswanta Siswanta (Universitas PGRI Yogyakarta, 2022)
ABSTRACTThe purpose of this study is to find out: (1) The Role of Public Kitchens during Dutch Military Aggression II (2) Factors of organizing Public Kitchens during Dutch Military Aggression II (3) Constraints in the implementation of Public Kitchens during Dutch Military Aggression II (4) The impact of the implementation of Public Kitchens during Dutch Military Aggression II. The method used in this study is qualitative research method. This research has two types of data and data sources, namely primary data, data obtained through direct interviews and secondary data, data in the form of journals and books. Data collection techniques by conducting live observations, in-depth interviews, and documentation. Data analysis techniques are used by data collection, data reduction, data presentation and conclusion drawing. The techniques of checking the validity of the data used are source trianggulation techniques and theoretical trianggulation. The results of this study show that: (1) The role of the Common Kitchen to meet the food of soldiers and civillian, the headquarters of military, emergency hospital. (2) The organizing factor of the Public Kitchen is due to the scarcity of foodstuffs due to aggression and the number of refugees. (3) The constraints of the implementation of the Public Kitchen are the scarcity of foodstuffs and the presence of Dutch spies. (4) The impact of the implementation of the Public Kitchen is that logistics needs are met, there is a sense of security in the civilian, and the establishment of village security agency. Keywords: Common Kitchen, Dutch Military Aggression II, Role